2018
DOI: 10.1007/s00408-018-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Integration of Cough and Swallow to Maintain Airway Protection in Humans

Abstract: These results give insight into the differences between the cat and human models in airway protective strategies related to the coordination of cough and swallow behaviors, allowing for better understanding of dystussia and dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 43 publications
3
24
2
Order By: Relevance
“…This study showed reliable integration of cough and swallow, an increase in cough epochs and an increase in inspiratory and compression phase duration during the combined stimuli protocol. The most interesting finding of this study was the participants' ability to swallow in any phase of cough, unlike the cat, to maintain a certain range of lung volume during eupnea and repetitive cough (Huff, Reed, Smith, Brown, Ovechkin, & Pitts, 2018b). This indicated that volume targeting may play a larger role than phase preference.…”
Section: Coordination Of Cough and Swallowmentioning
confidence: 73%
See 4 more Smart Citations
“…This study showed reliable integration of cough and swallow, an increase in cough epochs and an increase in inspiratory and compression phase duration during the combined stimuli protocol. The most interesting finding of this study was the participants' ability to swallow in any phase of cough, unlike the cat, to maintain a certain range of lung volume during eupnea and repetitive cough (Huff, Reed, Smith, Brown, Ovechkin, & Pitts, 2018b). This indicated that volume targeting may play a larger role than phase preference.…”
Section: Coordination Of Cough and Swallowmentioning
confidence: 73%
“…Despite the progress that has been made in the last century to understand the complex behavior of swallow, our mechanistic understanding of this important behavior is limited. Classically, swallow has been regarded as a strictly brainstem-mediated behavior, but more recent studies have determined that afferent feedback is important in the coordination of swallow with breathing cycle (Huff, Reed, Smith, Brown, Ovechkin, & Pitts, 2018b;McFarland, Martin-Harris, Fortin, Humphries, Hill, & Armeson, 2016;Wheeler Hegland, Huber, Pitts, Davenport, & Sapienza, 2011b;. In the cat, swallow normally occurs in the late expiratory (E2) phase of the cough breathing cycle , but upper abdominal laparotomy produces a significant shift of swallow to the inspiratory phase of the breathing cycle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations